Clinical Symptoms of Cholelithiasis and Abdominal Ultrasound Findings in the Radiology Installation of RSD - Dewi Darmayanti; Liasari Armaijn; Nani Supriyatni (GLOBAL HEALTH SCIENCE GROUP, 2025)
Cholelithiasis is one of the main causes of abdominal pain morbidity worldwide. The prevalence of cholelithiasis in developed countries is around 10-15% of the adult population, while in Asian countries the epidemiology of cholelithiasis ranges from 3-10%, with the prevalence of cholesterol cholelithiasis. This study aims to determine the relationship between clinical symptoms of cholelithiasis and abdominal USG findings at the radiology installation of Tidore Islands City Hospital. Methods: The type of research is observational with a cross-sectional study design. The research was conducted at the Radiology Installation of RSD Kota Tidore Kepulauan. The research sample consisted of 104 patients, with a total sampling method. Data were collected using secondary data obtained from the medical records of patients showing clinical symptoms of cholelithiasis from January to December 2023. data analysis used the Fisher’s exact test statistical method. Results and Discussions: The results of the study showed that the characteristics of patients aged 46-65 years were 50 people (48.1%), female gender was 66 people (63.5%), the largest patient clinical was cholelithiasis as many as 98 people (94.2%), the largest patient ultrasound findings were cholelithiasis as many as 98 people (94.2%), the results of the correlation between clinical cholelithiasis and ultrasound findings showed that clinical cholelithiasis with ultrasound findings of cholelithiasis was the most with a total of 95 people. The results of the Fisher's exact test obtained a p value = 0.002, which means that there is a correlation between clinical cholelithiasis and ultrasound findings of cholelithiasis.